2010
DOI: 10.4061/2010/759109
|View full text |Cite
|
Sign up to set email alerts
|

First Report of a Case with Needle Track Sinus after Aspiration Biopsy of a Benign Thyroid Nodule Resulted in an Unexpected Postoperative Complication

Abstract: Fine needle aspiration biopsy is the most feasible, safe, and accurate diagnostic tool for thyroid nodule diagnosis. The development of a sinus tract between thyroid gland and the skin through needle tract after fine needle aspiration biopsy is an extremely uncommon phenomenon. In this paper, a 71-year-old man presenting with a swelling and discharge on the anterior neck wall was reported. Similar complaints were present 15 to 20 days after fine needle aspiration biopsy of thyroid gland four years ago. Bilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Besides, other rare complications have also been reported as case reports. These are intrathyroidal massive hemorrhage and upper respiratory tract congestion [ 11 ], nodule infarction [ 12 ], recurrent laryngeal nerve palsy [ 13 ], tracheal injury related hemoptysis, thyrocutaneous sinus formation [ 14 ], and pleural injury resulting in pneumothorax [ 15 ]. Recent studies showed that using USG guided FNAB has significantly decreased the ratio of insufficient cytology reports comparing to the palpation guided FNAB [ 16 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, other rare complications have also been reported as case reports. These are intrathyroidal massive hemorrhage and upper respiratory tract congestion [ 11 ], nodule infarction [ 12 ], recurrent laryngeal nerve palsy [ 13 ], tracheal injury related hemoptysis, thyrocutaneous sinus formation [ 14 ], and pleural injury resulting in pneumothorax [ 15 ]. Recent studies showed that using USG guided FNAB has significantly decreased the ratio of insufficient cytology reports comparing to the palpation guided FNAB [ 16 18 ].…”
Section: Discussionmentioning
confidence: 99%